The reconstruction of slavery in the novel Chains by Laurie Halse Anderson: A post-nationalism perspective - Rosma Kadir; Nur Saktiningrum; Muh. Arif Rokhman (NOTION: Journal of Linguistics, Literature, and Culture, 2026)
This research examines Laurie Halse Anderson’s Chains as a counter-narrative to dominant representations of the American Revolution as a universal project of freedom. It employs Stuart Hall’s theory of representation and a qualitative textual analysis approach. This study explores how the novel reconstructs slavery as an ideological structure that shapes and limits the meaning of revolutionary liberty. The findings show that Chains constructs a genealogy of slavery as a foundation of the American Revolution and represents freedom as a selective and racialized political project. Slavery is portrayed as a system of human commodification that is transnational in nature and legitimized by law and colonial economic practices. Racial stereotypes operate ambivalently by dehumanizing enslaved people while simultaneously opening spaces for agency and resistance. The character Isabel is represented as a rational subject who can read, interpret, and appropriate the discourse of freedom for self-liberation. This article concludes that Chains critically and ethically reconstructs the memory of the American Revolution beyond the boundaries of the nation-state.